Evaluation by re-derivation of a paternal line after 18 generations on seminal traits, proteome and fertility - Juárez, Jorge D.; Marco-Jiménez, Francisco; Talavan, Amparo; García-Domínguez, Ximo; Viudes-De-Castro, María P.; Lavara, Raquel; Vicente, José Salvador (Elsevier, 2020)
Males from a paternal line selected for growth traits were used to produce semen doses at insemination centres and farms in a breeding scheme for rabbit meat production. The aim of this study was to assess whether a program of selection by daily gain in fattening period changed the seminal traits, plasma and sperm proteome and the fertility of semen when used in artificial insemination. Thirty-nine males from a paternal line were obtained by re-derivation from vitrified embryos with a difference of 18 generations (G21V and G39V). Sperm production parameters, morphological traits, sperm motility parameters and viability were evaluated from ejaculates. Seminal plasma and sperm proteome of three pool ejaculates from 10 mature males of each group were analysed and semen doses were used to inseminate 311 females. Only the percentage of abnormal sperm showed significant differences, with G21V presenting fewer abnormal sperm than G39V (10.5 ± 2.63 vs 23.8 ± 1.98). The discriminant analysis (DA-PLS) showed a clear effect of the generation for plasma and sperm proteome. In seminal plasma, 643 proteins were reported and 64 proteins were differentially expressed, of which 56 were overexpressed in G39V (87.5%). Sperm proteome reported 1360 proteins with 132 differentially abundant proteins. Of the total, 89 proteins were overexpressed in G39V (67.4%). From the 64 and 132 differentially abundant proteins of plasma and sperm, 19 and 26 had a FC>1.5, 12 and 13 of them belonging to the Oryctolagus cuniculus taxonomy, respectively. Despite observing differences in important proteins related to capacitation, sperm motility or immunoprotection and consequently to the fertilization process (TMPRSS2, Serpin family, Fam71f1, ATPase H+ transporting accessory protein 2, carbonic anhydrase 2, UDP-glucose glycoprotein glucosyltransferase 2), no differences in fertility and prolificacy were detected when commercial seminal doses were used for insemination from both male groups. However, overabundance of KIAA1324 protein can be related to the increase in abnormal sperm after selection by growth rate.